Fractional Programming Approach to a Cost Minimization Problem in the Electricity Market - Gruzdeva, Tatiana; Enkhbat, Rentsen; Tungalag, Natsagdorj (Yugoslav Journal of Operations Research; Vol 29 No 1 (2019), 2018)
This paper was motivated by a practical optimization problem that appeared in electricity market of Mongolia. We consider the total average cost minimization problem of power companies of the Ulaanbaatar city. By  solving an identification problem, we develop a fractional model  that quite adequately represents the real data. The problem obtained turned out to be  a fractional minimization problem over a  box constraint. To solve the problem, we propose a method that employs the global search theory for d.c. minimization.